PRINCIPLE OF VALIDATION OF MULTILEVEL RGB COLORIMETRIC SYSTEMS OF REMOTE SENSING - Bekirova, Lala Rustam (Proceedings of National Aviation University (archive), 2014)
The possibility of development of two-level RGB colorimetric systems of remote sensing is analyzed. The principle of validation in multi-level RGB colorimetric systems taking into account the effect of metamerizm is formulated